5z-(7x+7)=9

Simple and best practice solution for 5z-(7x+7)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5z-(7x+7)=9 equation:


Simplifying
5z + -1(7x + 7) = 9

Reorder the terms:
5z + -1(7 + 7x) = 9
5z + (7 * -1 + 7x * -1) = 9
5z + (-7 + -7x) = 9

Reorder the terms:
-7 + -7x + 5z = 9

Solving
-7 + -7x + 5z = 9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + -7x + 7 + 5z = 9 + 7

Reorder the terms:
-7 + 7 + -7x + 5z = 9 + 7

Combine like terms: -7 + 7 = 0
0 + -7x + 5z = 9 + 7
-7x + 5z = 9 + 7

Combine like terms: 9 + 7 = 16
-7x + 5z = 16

Add '-5z' to each side of the equation.
-7x + 5z + -5z = 16 + -5z

Combine like terms: 5z + -5z = 0
-7x + 0 = 16 + -5z
-7x = 16 + -5z

Divide each side by '-7'.
x = -2.285714286 + 0.7142857143z

Simplifying
x = -2.285714286 + 0.7142857143z

See similar equations:

| 3N+2b=c | | 4x+(-4)=-6 | | 11-8x=51-36x | | -144-7x=10x+22 | | 5x^3+2x^2+8x-10=0 | | 4v-5v=-4 | | 9a-4=41 | | 9a-4=4 | | 5x+1x=-3 | | 4(3x+2)-4= | | x^3-3x^2-7x+a=0 | | 3x=25-y | | 5=4x-9+x-3x | | X-4=0.5X | | 100=2x-x+4x | | 1/2(18-5x)=1/3(6-4x) | | 3x-5y=-18 | | x+15+3=25+10 | | 16d=8 | | 12x-17-9=4 | | 9x+5-(3x+3)=32 | | 2x*34x= | | 10b-13b+20b= | | 85-2x=97-3x | | 12=(30*x)/(30+x) | | 2x+12=4x-50 | | 12=30*x/(30+x) | | 12=30*x/30+x | | 12=30*x/30*x | | (x-5)+(x-3)+x+(x+5)=29 | | 2a-b+3a+4b= | | 42x+51-17x+23=182+13x |

Equations solver categories